PENGEMBANGAN MODUSIKU (E-MODUL DAN ASESMEN INTERAKTIF BERBASIS LITERASI KEARIFAN LOKAL KUDUS) SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA DAN KARAKTER - Setiawaty, Rani; Najikhah, Fatikhatun; Wijayanto, Wasis; Kironoratri, Lintang (Universitas Negeri Medan, 2025)
The objectives of this research are (1) to develop Modusiku (e-modules and interactive assessments that are integrated and based on local wisdom literacy) for Indonesian language learning and student character; (2) to test the validation of Modusiku; (3) to test the practicality of Modusiku. This research method is Research and Development with ADDIE model. Based on the results of the study, it shows that first, Modusiku as a medium for learning language and student character have been developed. Second, the results of the media expert validation test scored 81.55% (very feasible), the material expert 80% (very feasible), and the practitioner expert 84% (very feasible). Third, based on the results of the practicality test, it shows that this e-module is very practical to use in learning, with positive responses from teachers by 86% and students by 96%. Thus, Modusiku that has been improved based on the validator's input is considered feasible and practical as a medium for learning Indonesian as well as an effort to instill the character of love for local culture to students.